Caregiving burden and uplifts: A contradiction or a protective partnership for the quality of life of parents and their children with asthma? - Silva, Neuza (2015)
Introduction. Parental caregiving in the context of pediatric chronic conditions is a multifaceted experience that encompasses negative (burdens) and positive dimensions (uplifts), which may support risk and protective processes that influence family adaptation. This study aimed to examine the caregiving experience of parents caring for a child with asthma and the moderating role of caregiving uplifts on the associations between caregiving burden and quality of life (QoL) of parents and their children. Method. Participants were 180 dyads of children/adolescents with asthma between 8 and 18 years of age and one of their parents. The parents reported on caregiving burden and uplifts and on their QoL, and the children/adolescents completed a self-report measure of generic QoL. Results. Results showed that although parents of children with intermittent asthma and parents of younger children presented higher levels of caregiving burden, non-controlled asthma was the only clinical variable representing a significant risk factor for decreased QoL in children. Significant negative and positive associations were found between burden dimensions and QoL and between caregiving uplifts and QoL, respectively, in parents and children. Additionally, caregiving uplifts moderated the negative link between relationship burden and parents’ QoL. Conclusion. These results suggest that, far from being contradictory, caregiving uplifts may co-occur with high levels of burden and may constitute a protective factor against the deleterious effect of the caregiving burden on parents’ QoL and a resource that directly contributes to children’s QoL. This risk-resistance approach to family caregiving may contribute to operationalizing strength-based interventions in the context of pediatric asthma.